Assessment of the optimal timing for early laparoscopic cholecystectomy in acute cholecystitis: a prospective study of the Club Coelio. Issue 5 (3rd September 2019) - Brunée, L.; Hauters, P.; Closset, J.; Fromont, G.; Puia-Negelescu, S.
Abstract: Background : The optimal timing for cholecystectomy in patients with acute cholecystitis remains controversial. The aim of this study is to assess prospectively the impact of the duration of symptoms on outcomes in early laparoscopic cholecystectomy (ELC) for acute cholecystitis. Methods : The series consisted of 276 consecutive patients who underwent ELC for acute cholecystitis in 2016. The patients were divided into three groups according to the timing of surgery: within the first 3 days (group 1), between 4 and 7 days (group 2) and beyond 7 days (group 3) from the onset of symptoms. Results : The percentage of surgical procedure rated as difficult was respectively: 12% in G1, 18% in G2 and 38% in G3 ( p < .001). Accordingly, we observed an increased mean operative time within groups but no significant difference in the conversion rate. We noted a different overall postoperative complication rate within groups, respectively: 9% in G1, 14% in G2 and 24% in G3 ( p < .04). The median hospital stay was also different within groups, respectively: 3 in G1, 4 in G2 and 6 days in G3 ( p < .001). On univariate analysis, age ≥60, male gender, ASA 3, WBC ≥13.000/µL, CRP ≥100 mg/l and delay between onset of symptoms and surgery were factors statistically associated with increased morbidity rate. On multivariate analysis, the delay was the only independent predictive factor of postoperative morbidity (OR: 1, 08, 95% CI: 1.01–1.61, p < .031). Conclusion : Our study confirms that it is ideal to perform ELC within 3 days of symptoms onset and reasonable between 4 to 7 days. We do not recommend performing ELC beyond 7 days because of more difficult procedure and significantly increased risk of post-operative complications.